2019
DOI: 10.31234/osf.io/6qayb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inaccurate group meta-perceptions drive negative out-group attributions in competitive contexts

Abstract: Across seven experiments and one survey (N=4282) people consistently overestimated out-group negativity towards the collective behavior of their in-group. This negativity bias in group meta-perception was present across multiple competitive (but not cooperative) intergroup contexts, and appears to be yoked to group psychology more generally; we observed negativity bias for estimation of out-group, anonymized-group, and even fellow in-group members’ perceptions. Importantly, in the context of American politics … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 0 publications
4
69
1
Order By: Relevance
“…In fact, recent research provides evidence that correcting ideological polarization between political partisans effectively reduces negative intergroup outcomes (Lees & Cikara, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent research provides evidence that correcting ideological polarization between political partisans effectively reduces negative intergroup outcomes (Lees & Cikara, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a longitudinal study demonstrated that daily exposure to political situations was associated with worse physical and mental well-being (Feinberg et al, 2020). Additionally, exposure to hateful content can decrease social trust (Näsi et al, 2015) and exaggerate the feeling of outgroup threat (Lees & Cikara, 2020), which could add to negative well-being outcomes. Further work should examine the consequence of engaging in political discourse online on users' well-being.…”
Section: Implications Of the Findingsmentioning
confidence: 99%
“…from "not at all respectful" to "very respectful." We developed this measure in light of recent research suggesting the importance of meta-perception in explaining, and reducing, political polarization (Lees and Cikara, 2020).…”
Section: Outcome Variables and Other Measuresmentioning
confidence: 99%